Neurodegenerative disorder risk in idiopathic REM sleep behavior disorder: study in 174 patients. - Alex Iranzo; Ana Fernández-Arcos; Eduard Tolosa; Mónica Serradell; José Luis Molinuevo; Francesc Valldeoriola; Ellen Gelpi; Isabel Vilaseca; Raquel Sánchez-Valle; Albert Lladó; Carles Gaig; Joan Santamaría (PLoS ONE, 2014)
Objective To estimate the risk for developing a defined neurodegenerative syndrome in a large cohort of idiopathic REM sleep behavior disorder (IRBD) patients with long follow-up. Methods Using the Kaplan-Meier method, we estimated the disease-free survival rate from defined neurodegenerative syndromes in all the consecutive IRBD patients diagnosed and followed-up in our tertiary referal sleep center between November 1991 and July 2013. Results The cohort comprises 174 patients with a median age at diagnosis of IRBD of 69 years and a median follow-up of four years. The risk of a defined neurodegenerative syndrome from the time of IRBD diagnosis was 33.1% at five years, 75.7% at ten years, and 90.9% at 14 years. The median conversion time was 7.5 years. Emerging diagnoses (37.4%) were dementia with Lewy bodies (DLB) in 29 subjects, Parkinson disease (PD) in 22, multiple system atrophy (MSA) in two, and mild cognitive impairment (MCI) in 12. In six cases, in whom postmortem was performed, neuropathological examination disclosed neuronal loss and widespread Lewy-type pathology in the brain in each case. Conclusions In a large IRBD cohort diagnosed in a tertiary referal sleep center, prolonged follow-up indicated that the majority of patients are eventually diagnosed with the synucleinopathies PD, DLB and less frequently MSA. IRBD represented the prodromal period of these conditions. Our findings in IRBD have important implications in clinical practice, in the investigation of the early pathological events occurring in the synucleinopathies, and for the design of interventions with potential disease-modifying agents.